Caracterización del Sistema Productivo de Ovinos en el Centro Experimental Academico Salache CEASA - Guevara Inga, Carlos Andrés (2019)
The present investigation was carried out in the Unversidad Tecnica de Cotopaxi at Salache Academic experimental Center located in the Cotopaxi province, at Eloy Alfaro parish in Salache Bajo neighbourhood. It was made the ovine production characterization system that involves the flora and fauna components. This Project focus on the different levels of development from the bibliographic collection, field data and lab analysis. To the plant component a bromatologic exam was practice in which the the proximal analysis , van Soest and mineralswere added. The results show a low weight gaining due to 28 ovines that were level between adult female, young and male, only 3 animals got gaining , giving like result an average of 16,7 grames; this weight gaining is was made by a register formula in Excel where two weight were needed in which it was detracted and divided for 15 days and multiply for 1000 to get the result of a daily gaining